Fatigue and team performance in soccer: Evidence from the FIFA World Cup and the UEFA European Championship - Scoppa, V. (Discussion Paper Series, 2013)
We investigate the role of fatigue in soccer (football). Although this issue is important for the "productivity" of players and the optimal organization of national and international championships, empirical evidence is lacking. We use data on all the matches played by national teams in all the tournaments of the FIFA Soccer World Cup (from 1930 to 2010) and the UEFA European Football Championship (from 1960 to 2012). We relate team performance (in terms of points gained and goals scored and conceded) to the respective days of rests that teams have had after their previous match, controlling for several measures of teams` abilities. Using different estimators we show that, under the current structure of major international tournaments, there are no relevant effects of enjoying different days of rest on team performance. However, we find that before Nineties days of rest had a positive impact on performance, presumably because athletic preparation of players was less effective. Furthermore, we show that the advantage of additional rest is quite relevant, when rest time of one of the opposing teams is three days or less.